Characterization Analysis and the Feminism Reflection Of Jo March in the Little Women Movie - Ade Lia Putri; Luqman Al Hakim (English Education Department Slamet Riyadi University Surakarta, 2023)
The purpose of this study is to analyze the characterization and the feminism reflection of Jo March in the Little Women movie. This study employed a feminist perspective and was descriptive qualitative research. Greta Gerwig's script and direction of the Little Women film served as the basis for the information. Jo March is a young middle-class woman with a tall physique, brown hair, and grey eyes, according to the findings of this study. An ambitious, independent, grumpy, smart, clumsy, and caring individual is how Jo March was described. By proving her independence and capacity for comfortable living without being married to a wealthy man, she defies the stereotype. She published her book under her own name and actively took part in the then-current battle for women's rights in the public sphere.Keywords: Character, Characterization, Feminism, Gender Equality